Telaah Konsep Pendidikan Ibadah dalam Al-Qur’an - Karjaya, Ikrima Nur Ilmy; Nuha Salwa Salsabila; Lystia Desti Sukma; Andriani Andriani; Irna Hasanah (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
This study was conducted based on the idea that understanding the values of worship contained in the Qur'an plays an important role in shaping the faith, obedience, and religious behavior of Muslims. Worship education is not only related to the formal and ritual implementation of religious commands, but also significantly influences the formation of attitudes, personality, and character in daily life. Therefore, an in-depth study of the ideas and foundations of worship education in the Qur'an is necessary so that these values can be properly understood and applied, especially in the field of education. This research employs a qualitative method with a literature study approach, focusing on the analysis of Qur'anic verses related to worship. It is supported by various sources such as tafsir books, Islamic education literature, and relevant scientific references. The findings indicate that worship education in the Qur'an emphasizes strengthening faith in Allah, developing consistency in worship practices, and fostering noble character. Furthermore, worship education helps balance the relationship between humans and the Creator while also enhancing social interactions among individuals. The values of worship contribute to the development of spiritual awareness, discipline, moral responsibility, and positive social behavior. In conclusion, worship education based on the Qur'an serves as a fundamental foundation for shaping Muslims who are faithful, possess good character, and are able to practice Islamic values comprehensively in their daily lives.